PARALLEL COORDINATE APPLICATION IN 4 DIMENSION ROOM AT PLANE TRAFFIC DISPLAY - Hartono, Hartono; Krisnawan, Kus Prihantoso; Arifah, Husna (Yogyakarta State University, 2015)
This research aims to describe ann-dimensional line on a parallel coordinate and uses the representation as a display of aircraft motion which flies at a straight line and constant velocity. A parallel coordinate of n-dimensional space depicted in the form of nparallel vertical lines which represent axis.Every two adjacent axes have the same distance. A horizontal line that cutsall axes indicates the initial pointsof each axis. In a parallel coordinate,an 15n